MiR-19-3p Promotes Autophagy and Apoptosis in Pelvic Organ Prolapse Through the AKT/mTOR/p70S6K Pathway: Function of miR-19-3p on Vaginal Fibroblasts by Targeting IGF-1. Issue 9 (September 2021) - Yin, Yitong; Qin, Meiying; Luan, Meng; Xia, Zhijun
Abstract : Objective: Pelvic organ prolapse (POP) is a common condition in older women. A decrease in collagen 1 (Col-1) expression is one of the main causes of POP. Many microRNAs play an important role in regulating target genes. The relationship between miR-19-3p and POP is investigated in this study, and the molecular mechanism was also explored to find whether miR-19-3p may be a potential target for early diagnosis and prevention of POP. Methods: A total of 60 patients with POP and 60 patients without POP were included in this study. Reverse transcription-polymerase chain reaction and Western blot were used to detect the expression of miR-19-3p, insulin-like growth factor 1 (IGF-1), and the Akt/mTOR/p70S6K pathway. Cell cycle was defined by flow cytometric analysis. The combination of miR-19-3p and IGF-1 was revealed by luciferase assays. Results: The results of this study show that miR-19-3p was upregulated in the tissue of patients with POP, whereas COL-1 and IGF-1 expressions were lower in the POP group. miR-19-3p promoted excessive fibroblast autophagy and apoptosis. miR-19-3p negatively regulated the Akt/mTOR/p70S6K pathway and inhibited COL-1 secretion. Luciferase reporter assay showed that miR-19-3p regulated IGF-1 expression by direct target binding. Conclusions: miR-19-3p has negative associations with the expression of Col-1. Our study highlights that miR-19-3p may affect the synthesis of Col-1 by targeting IGF-1 and that it may play an vital role in POP.